The activity of the national democratic party of Germany and the authorities' attempts to recognize the party unconstitutional (1998-2006) - Artem Yovenko (Cхід)
The article deals with the place and role NPD in German politics, reaction to NPD activities of public authorities and society, progress and consequences of the proceedings on the Prohibition Party and the development of relations with other right parties.